Intra-operative low-dose ketamine versus dexmedetomidine for attenuation of acute postoperative pain following laparoscopic cholecystectomy: a randomized clinical trial - Naorem, Sonia; Sharma, Bobby B.; Laithangbam, Pradipkumar S.; Ngangom, Bidya; Sankar, Arivumadhi; Yimchunger, Dojingla; Kumar, Prem P. (International Journal of Research in Medical Sciences, 2026)
Background: Ketamine and dexmedetomidine are opioid-sparing agents with distinct analgesic properties. Ketamine is valued for its ability to prevent central sensitization and hyperalgesia without causing respiratory depression. Dexmedetomidine exhibits sedative, anxiolytic, analgesic, anaesthetic, and sympatholytic effects. This study hypothesized that a low-dose combination of ketamine and dexmedetomidine would offer superior analgesia compared to either agent alone when used as an adjuvant during balanced general anaesthesia. Methods: Sixty patients scheduled for elective laparoscopic cholecystectomy under general anaesthesia were randomized into four groups group D: dexmedetomidine 0.25 μg/kg i.v., group K: ketamine 0.25 mg/kg i.v., group DK: combination of dexmedetomidine and ketamine at the same doses, group S: normal saline. All drugs were diluted to 5 ml and administered intravenously 20 minutes before anticipated skin closure. Postoperative VAS scores and sedation were assessed. The time to first rescue analgesia and total diclofenac consumption over 24 hours were documented. Results: Postoperatively, group DK demonstrated significantly lower VAS scores at rest and during movement across multiple time points compared to the other groups (p<0.05). The combination group also had the longest time to first rescue analgesia and the lowest total diclofenac requirement. No significant adverse effects were reported in any of the groups. Conclusions: A low-dose combination of ketamine and dexmedetomidine administered prior to skin closure in laparoscopic cholecystectomy significantly improves postoperative analgesia without increasing side effects. This combination appears to be a safe and effective strategy for enhancing pain control following laparoscopic cholecystectomy.